Pengaruh Kinerja Guru Lingkungan Sekolah Dan Media Pembelajaran Terhadap Hasil Belajar - Syarifuddin Syarifuddin; Nur Hasnah; Abdul Rahman Abdi (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2023)
The objectives of this study (1) the influence of teacher performance, school environment, and learning media partially and simultaneously on student learning outcomes (2) the most dominant variables affect student learning outcomes. This research uses quantitative descriptive method. The data used are primary and secondary data generated from the dissemination of questionnaires, observations, and document records. The analysis used is statistical analysis, namely multiple linear regression analysis with hypothesis proof through the t test to partially prove the relationship between independent variables and dependent variables and theF-test to prove the relationship between independent variables and dependent variables simultaneously. The population in the research amounted to 500 students (classes X, XI, and XII), and 40 respondents were selected so that the number of samples was 120 students (40 students of class X, 40 class XI and 40 class XII) with sampling techniques using Purposive sampling The results of this study showed that (1) teacher performance did not affect student learning outcomes while, the school environment, and learning media have a positive and significant effect on student learning outcomes (2) Teacher performance, school environment, and learning media have a simultaneous effect on student learning outcomes (3) the school environment is the most dominant variable affecting student learning outcomes.